INTERELASI AGAMA DAN BUDAYA - Pangulu Abdul Karim (Universitas Islam Negeri Sumatera Utara, 2016)
Religion and culture has a very strong relationship, because both of them are values and symbols. Religion is a symbol that represents the value of obedience to God. Culture also contain values and symbols so that people can live in the environment. However, it should be emphasized that there is a difference. Religion is already final, eternal, and does not recognize the change. Meanwhile the culture can change. But both are able to shift due to both an historical fact.Kata Kunci: Interelasi, Agama, Budaya